Efforts to Overcome Child Commercial Sexual Exploitation Victims in City Tourism Area, Manado - Rahmat Hidayat; Budiman Rusli; Sintaningrum Sintaningrum; Yogi Suprayogi Sugandi (Policy & Governance Review, 2017)
The tourism sector has a significant contribution to the economy of Manado City, North Sulawesi Province. However, on the other hand, it has a negative effect on the increase in the number of child commercial sexual exploitation victims and makes children into commercial sex workers. Despite not effective, the Local Government of Manado City, North Sulawesi Province, has made efforts to cope with the child commercial sexual exploitation victims. In connection with the case, this study is designed to analyze the causes of ineffectiveness of Local Government efforts in tackling child commercial sexual exploitation victims. The study was conducted in tourism area of Manado City, North Sulawesi Province. The informants involved in this study were divided into two types: experts and non-experts. The informants were determined by using Opportunistic Sampling, and the sampling is using Snowball Sampling. The results of the study showed that the development of tourism sector has negative effect on children in the communities. Efforts made to cope with child commercial sexual exploitation victims by the local government and relevant parties have not been effective due to limited allocation of budgets and skilled, quality human resources, the lack of harmonious understanding between police with judges and public prosecutors as law apparatus, supervision, and protection of victims in solving the cases of child commercial sexual exploitation victims, the implementation of action committee’s duties and responsibility have been not effect, the number of obstacles facing them.